Cost-effectiveness analysis of tislelizumab, nivolumab and docetaxel as second- and third-line for advanced or metastatic non-small cell lung cancer in China - Zhou, Dongchu; Luo, Xia; Zhou, Zhen; Zeng, Xiaohui; Wan, Xiaomin; Tan, Chongqing; Liu, Qiao (Frontiers in Pharmacology, 2022)
Objective Domestic PD-1inhibitor tislelizumab has emerged as a promising treatment for Chinese patients with driver-negative advanced or metastatic non-small cell lung cancer (NSCLC). The purpose of our study to evaluate whether tislelizumab is cost-effective as a second- or third-line treatment for this population compared with docetaxel (conventional chemotherapy) and nivolumab (imported PD-1inhibitor), from the perspective of the Chinese healthcare system. Material and Methods A Markov model with a 3-week Markov cycle and a 30-year time horizon was built to compare the cost-effectiveness of second- or third-line tislelizumab versus docetaxel and nivolumab. Transition probabilities, including disease progression, survival, and adverse events (AEs)-related treatment discontinuation event, were estimated from the clinical trials. Costs and health utilities were collected from local hospitals, public database and published literature. Results Compared with docetaxel, tislelizumab provided an additional 0.33 quality-adjusted life-years (QALYs) (1.37 vs 1.04 QALYs) at an incremental cost of $9,286 ($23,646 vs $14,360) for Chinese patients with driver-negative advanced or metastatic NSCLC, resulting in an incremental cost-effectiveness ratio (ICER) of $27,959/QALY under the WTP threshold of $35,663/QALY used in the model. Compared with nivolumab, tislelizumab was associated with a lower cost ($23,646 vs $59,447) and higher QALYs (1.37 vs 1.20 QALYs), resulting in its dominance of nivolumab. Conclusion From the perspective of the Chinese healthcare system, domestic PD-1inhibitor tislelizumab immunotherapy represents a cost-effective treatment strategy compared with conventional docetaxel chemotherapy and imported PD-1inhibitor nivolumab immunotherapy in the treatment of driver-negative advanced or metastatic NSCLC beyond the first-line setting. In the era of “Universal Medical Insurance System”, the rational use of domestic anticancer drugs guided by cost-benefit evidence would be an effective means to balance the limited expenditure of medical insurance fund and the growing demand for cancer treatments.